2016
DOI: 10.1103/physrevb.93.214424
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the critical Fe atomic volume on the magnetism of Fe-rich metallic glasses evidenced by pressure-dependent measurements

Abstract: Despite the intensive studies for decades, it is still not well understood how qualitatively different magnetic behaviors can occur in a narrow composition range for the Fe-rich Fe-transition metal (TM) amorphous alloys. In this study of amorphous Fe 100−x Zr x (x = 7, 9, 12) metallic glasses, normal ferromagnetism (FM) is found at 12 % Zr where only the FM-paramagnetic (PM) transition is observed at the Curie temperature, T C . In contrast, spin-glass (SG)-PM transition at a temperature, T g , called SG tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…The deviation from linear correlation is due to the fact that Fe 80 P 9 B 11 amorphous alloy is just a weak ferromagnet so that the magnetic moment is sensitive to the Fe-Fe atomic distance. This can also explain that Co 91 Zr 9 manifests an almost pressure-independent magnetic behavior, while the magnetic property of Fe 91 Zr 9 shows an extreme sensitivity to volume change [14] in this simple method. According to the relevant work, [15] Fe atom pairs with longer distance are supposed to have stronger ferromagnetic exchange, resulting in higher magnetic moment.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…The deviation from linear correlation is due to the fact that Fe 80 P 9 B 11 amorphous alloy is just a weak ferromagnet so that the magnetic moment is sensitive to the Fe-Fe atomic distance. This can also explain that Co 91 Zr 9 manifests an almost pressure-independent magnetic behavior, while the magnetic property of Fe 91 Zr 9 shows an extreme sensitivity to volume change [14] in this simple method. According to the relevant work, [15] Fe atom pairs with longer distance are supposed to have stronger ferromagnetic exchange, resulting in higher magnetic moment.…”
Section: Resultsmentioning
confidence: 69%
“…They found that the average magnetic moment generally follows a Slater-Pauling curve, and attributed the discrepancy to the weak ferromagnetic nature of bcc Fe. Recently, Kiss et al [14] investigated the anomalous magnetic behaviors of Fe-Zr metallic glasses in detail and elaborated this anomaly in terms of critical Fe atomic volume. Based on AIMD simulation of Fe 85 Si 2 B 8 P 4 Cu 1 (NANOMET) amorphous alloy, [15] it is revealed that magnetic moment is both electron charge dependent and atomic volume dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Since Duwze [1] discovered the first ferromagnetic metallic glass in Fe-P-C system, Fe-based metallic glasses have been attracted attention wildly because of the excellent soft magnetic properties, i.e., high saturation magnetization, low coercivity, and high permeability [2][3][4][5][6]. In particular, alloys based on the Fe-Si-B system in the amorphous states are used as the core materials for the transformers due to the good constant permeability and low eddy current losses [7].…”
Section: Introductionmentioning
confidence: 99%